2014
DOI: 10.1007/s13594-014-0175-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of volatile compounds produced by wild Lactococcus lactis in miniature Chihuahua-type cheeses

Abstract: International audienceStrains of Lactococcus lactis used for a long time as starter cultures in the production of cheese have not only acquired special features like fast utilization of lactose, but it is also believed that they have lost certain metabolic capabilities. Certain wild strains of L. lactis isolated from vegetables or raw milk products are able to generate flavors different from those produced by industrial strains. The aim of this work was to assess the production of volatile compounds in miniatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Manufacturing of artisanal Chihuahua cheese includes the use of unpasteurized milk, where autochthonous LAB contributes to the transformation of milk components thanks to enzymatic processes [24]. This transformation includes the generation of a particular flavor and texture.…”
Section: Discussionmentioning
confidence: 99%
“…Manufacturing of artisanal Chihuahua cheese includes the use of unpasteurized milk, where autochthonous LAB contributes to the transformation of milk components thanks to enzymatic processes [24]. This transformation includes the generation of a particular flavor and texture.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the production of diacetyl and acetoin varied by a factor >20 and 200, respectively (Alemayehu et al 2014). Differences between the amounts of acetoin produced by wild strains of L. lactis were also observed in miniature Chihuahua-type cheese (Nájera-Domínguez et al 2014). …”
Section: Formation Of Flavour Compounds By L Lactismentioning
confidence: 95%
“…2-methyl propanal (Griffiths, 2010) and 4-heptenal (Belitz et al, 2009), compounds previously found to be associated with milk aroma, were detected in this study. Benzaldehyde (Bourdat-Deschamps et al, 2004), 2-pentanone (Gallegos et al, 2017), hexanal (Gómez-Torres et al, 2016), 2,7-dimethyl-4,5-octanediol (Nájera-Domínguez et al, 2014) were previously described as secondary metabolites of LAB.…”
Section: Resultsmentioning
confidence: 99%